DETERMINAN NET INTEREST MARGIN BANK KONVENSIONAL DI INDONESIA - Nurfauziah, Farah Latifah; Sayekti, Fitria Ningrum (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2021)
This study investigated the internal and external factors that affecting factor of Indonesia conventional commercial bank’s net interest margin on quarterly data of 21 banks during 2016Q1 to 2018Q3. The results reveal several main drivers of net interest margin in Indonesia. We found that BI 7-Days reverse repo rate and the ratio of operating expenses to operating income affect net interest margin negatively, meanwhile equity to total assets ratio and banks size affect net interest margin positively. It is recommended that empirical studies should be undertaken in the same field to find out what more internal factors could affect bank’ net interest margin in Indonesia.